Surgical outcomes of mandibular fractures treated with miniplate fixation and management of teeth in the line of fracture - Giang, Trinh Truong; Dung, Vo Anh; Khue, Truong Nhut (Tạp chí Nghiên cứu Y học, 2026)
Tooth-bearing mandibular fractures require stable fixation while preserving teeth in the fracture line to restore function and reduce complications. This prospective single-arm interventional study evaluated outcomes of miniplate fixation and tooth management in 37 patients treated with open reduction and internal fixation at two hospitals in Dong Nai from July 2025 to March 2026, with 12 weeks of follow-up. Mean age was 33.1 ± 14.2 years old and 67.6% were male. After 12 weeks, good bone healing was achieved in 94.6% and correct occlusion in 97.3%, with no major complications. Maximum mouth opening improved significantly, with good outcomes increasing from 48.6% to 94.6% (p = 0.032). Among 58 teeth in the fracture line, 6 were extracted intraoperatively and 52 were preserved. At 4 and 12 weeks, 1 and 3 teeth required endodontic treatment, and no secondary extraction was needed. Overall, 91.9% of patients had good results, with 97.3%, 94.6%, and 91.9% satisfactory outcomes in anatomical, functional, and aesthetic domains. Miniplate fixation was effective for bone healing, functional recovery, and tooth preservation when appropriately managed.